Financial integration, international portfolio choice and the European Monetary Union - Roberto A. De Santis; Bruno Gérard (European Central Bank (ECB), 2006)
We investigate the determinants of bilateral international equity and bond portfolio reallocation across a large cross section of countries over the 1997 to 2001 period. We first argue that financial integration is not a global phenomenon, as equity and bond home biases declined significantly only among European countries, Australia, New Zealand and Singapore. Then, we show that the European Economic and Monetary Union (EMU) eased the access to the equity market and, to a larger extent, the bond market; thereby, enhancing regional financial integration in the euro area. Beside the effect of the EMU, the strongest determinants of the changes in portfolio weights are expected diversification benefits and the initial degree of underweight.
Keywords: C13; C21; F37; G11; 330; EMU; home bias; International portfolio weights; Risk diversification; Internationaler Finanzmarkt; Portfolio-Management; Eurozone; EU-Staaten; Welt; Entscheidung unter Risiko; Portfoliodiversifikation